(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: The purpose of this study was to assess the effect of bimaxillary orthognathic surgery on the short-term soft tissue changesof facial structures using a laser scanner for 3D facial acquisition.Materials and methods: Thirty patients were selected for this study with skeletal class III malocclusion that required bimaxillaryorthognathic surgeryA Le Fort I maxillary advancement with or without maxillary impaction and a bilateral sagittal split osteotomy were performed. 3Dacquisition of the craniofacial structures was obtained by Planmeca ProMax® laser surface scanner, preoperatively and postoperativelyafter 6 months.Result: These scans were superimposed over each other and was analyzed by the color-coded map. Bimaxillary orthognathic surgeryresulted in soft-tissue changes that were maximized in the central parts of the face than in the lateral parts.Conclusion: The color-coded analysis provides a better understanding of the three-dimensional soft tissue changes.